2011
DOI: 10.1002/art.30188
|View full text |Cite
|
Sign up to set email alerts
|

Association of a functional polymorphism in the 3′-untranslated region of SPI1 with systemic lupus erythematosus

Abstract: Objective. SPI1, also referred to as PU.1, is an Ets family transcription factor that interacts with IRF2, IRF4, and IRF8. In view of the significance of the type I interferon pathway in systemic lupus erythematosus (SLE), this study was undertaken to investigate a possible association between SPI1 polymorphisms and SLE.Methods. A case-control association study was performed using 6 tag single-nucleotide polymorphisms (SNPs), as well as a SNP located upstream of SPI1 previously found to be associated with acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 49 publications
3
36
0
Order By: Relevance
“…This is the first report to identify the importance of haploinsufficiency of IRF4 for disease resistance in autoimmune disease. This finding is highly critical from a clinical point of view, as it suggests the importance of subtle differences in IRF4 expression due to gene polymorphisms such as SPI1 for disease development or activity in systemic lupus erythematosus [40]. Similar results have been demonstrated in studies of mitogen-inducible gene 6 protein in streptozotocin-induced diabetes and in our previous study of IL-17 in autoimmune thyroiditis in NOD-H2 h4 mice [41,42].…”
Section: Discussionsupporting
confidence: 79%
“…This is the first report to identify the importance of haploinsufficiency of IRF4 for disease resistance in autoimmune disease. This finding is highly critical from a clinical point of view, as it suggests the importance of subtle differences in IRF4 expression due to gene polymorphisms such as SPI1 for disease development or activity in systemic lupus erythematosus [40]. Similar results have been demonstrated in studies of mitogen-inducible gene 6 protein in streptozotocin-induced diabetes and in our previous study of IL-17 in autoimmune thyroiditis in NOD-H2 h4 mice [41,42].…”
Section: Discussionsupporting
confidence: 79%
“…For example, the base transition of T to C at rs8126, a polymorphism located in the miRNA-binding site of TNFAIP2, was suggested to contribute in the up-regulation of TNFAIP2 in Head and Neck Squamous Cell Carcinoma (HNSCC) . Another study in systemic lupus erythematosus showed that rs1057233 in the 3′UTR of SPI1 was associated with the elevation of SPI1 mRNA level (Hikami et al 2011). Similar results were also found in ovarian cancer (Wynendaele et al 2010) and breast cancer (Zhang et al 2011).…”
Section: Discussionsupporting
confidence: 65%
“…A SNP rs1057233*T (T/C) in the 3′-UTR of SPI1 alters a target sequence for miR-569 that is associated with elevated SPI1 mRNA level and with susceptibility to SLE [28]. However, another variant rs57095329*G (G/A) in the promoter region of miR-146a primary transcript was associated with SLE in Chinese [29].…”
Section: Introductionmentioning
confidence: 99%